Biomass bimetallic catalyst and preparation method thereof
A biomass bimetallic catalyst with high crystallinity and porous structure is prepared from biomass and non-precious metals, addressing the inefficiencies of existing biomass utilization by achieving high reaction activity and selectivity in hydrodenitrogenation reactions.
Patent Information
- Application Number
- CN202411356442.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
AI Technical Summary
Existing biomass utilization technologies have low efficiency and do not fully exploit the potential of renewable biomass resources, leading to resource and environmental issues, and there is a need for an environmentally friendly and effective strategy to utilize biomass resources effectively.
A method is developed to prepare a biomass bimetallic catalyst using biomass, ammonium molybdate, and nickel nitrate hexahydrate, involving mixing, drying, grinding, carbonization, and passivation to produce a Ni-doped hexagonal phase Mo2C catalyst with high crystallinity and a porous structure, which is used in hydrodenitrogenation reactions.
The catalyst exhibits high reaction activity and aromatic compound selectivity in hydrodenitrogenation reactions, utilizing biomass waste as a low-cost raw material and providing additional nitrogen sources, enhancing electron distribution and active sites.
Smart Images

Figure CN119236983A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biomass energy conversion, and in particular to a biomass bimetallic catalyst and a preparation method thereof. Background Art
[0002] Due to the rapid consumption of non-renewable energy, the imbalance between supply and demand of fossil energy and environmental pollution have attracted wide attention, further promoting the development of sustainable, renewable and alternative energy. my country's biomass resources are rich and widely distributed. At the same time, with the expansion of afforestation area and the development of economy and society, the potential of my country's biomass resources to be converted into energy can reach 1 billion tons of standard coal. In the context of the depletion of traditional energy, biomass energy is an ideal alternative energy and is known as the "fourth largest" energy after coal, oil and natural gas. Biomass energy can be converted into conventional solid, liquid and gaseous fuels and is a renewable energy source. However, in the past development process, most biomass has been treated as waste and mostly treated by incineration. A large amount of forest residues, agricultural waste, fruit processing waste, and other food waste treatment, these types of waste will lead to serious resource and environmental problems. Therefore, it is crucial to develop an environmentally friendly and effective strategy to make high-value use of various types of biomass resources. Summary of the invention
[0003] In order to solve the above-mentioned deficiencies in the art, the present application aims to provide a biomass bimetallic catalyst and a preparation method thereof.
[0004] According to one aspect of the present application, there is provided a method for preparing a biomass bimetallic catalyst, comprising:
[0005] The biomass, ammonium molybdate and nickel nitrate hexahydrate are mixed and dried to obtain a catalyst precursor;
[0006] Grinding the catalyst precursor to obtain catalyst precursor powder;
[0007] The catalyst precursor powder is carbonized and passivated to obtain a biomass-based Ni-Mo2C catalyst.
[0008] According to some embodiments of the present application, the ratio of the amount of ammonium molybdate to the amount of nickel-molybdenum substance in nickel nitrate hexahydrate is 1:100-1:10;
[0009] The mass ratio of biomass to ammonium molybdate is 2:1-1:2.
[0010] According to some embodiments of the present application, the drying temperature is 60-100°C.
[0011] According to some embodiments of the present application, carbonization includes: carbonization at 650-900° C. for 1-3 h in an NH 3 atmosphere.
[0012] According to some embodiments of the present application, the heating rate of carbonization is 5°C / min.
[0013] According to some embodiments of the present application, the passivation includes: passivation with O2 having a volume concentration of 1% for 4-8 hours.
[0014] According to some embodiments of the present application, the biomass includes wood, straw, and food crops;
[0015] Optionally, the biomass powder size is less than 40 mesh.
[0016] According to another aspect of the present application, a biomass bimetallic catalyst is provided, the catalyst comprising: an active component and a carrier;
[0017] The carrier is biochar; the active component is Ni-doped Mo2C;
[0018] Among them, the molar ratio of nickel and molybdenum is 1:100-1:10, and the mass ratio of biomass and ammonium molybdate is 2:1-1:2.
[0019] According to some embodiments of the present application, the biomass bimetallic catalyst is a nanocatalyst;
[0020] The size of the biomass bimetallic catalyst is 3-5 nm.
[0021] According to another aspect of the present application, the biomass bimetallic catalyst is used in the hydrodenitrogenation reaction of bio-crude oil to produce aromatic compounds.
[0022] Compared with the prior art, this application has at least the following beneficial effects:
[0023] The present application provides a biomass bimetallic catalyst, which is a Ni-doped hexagonal phase Mo2C, with high crystallinity, rich and dispersed active sites, small particle size, fluffy and porous, and is a nano-sized catalyst with a porous structure. The catalyst of the present application has excellent reaction activity and aromatic compound selectivity in the reaction of hydrodenitrogenation of quinoline, a model compound of bio-crude oil, to produce aromatic compounds.
[0024] The present application provides a method for preparing a biomass bimetallic catalyst, using biomass, ammonium molybdate and nickel nitrate hexahydrate as raw materials, and preparing a biomass carbon-based Ni-Mo2C catalyst by carbonization reduction in an ammonia atmosphere. The preparation method of the present application is simple, and the raw materials are biomass waste and non-precious metal salts, which are low-cost and can be used for large-scale industrial preparation. The catalyst preparation process of the present application uses ammonia, which adds an additional nitrogen source compared to using hydrogen as a reducing gas, while reducing safety risks.
[0025] In addition to being a carrier, the biomass of the present application also provides a carbon source for the formation of carbides; at the same time, when the amino groups existing in the biomass itself are carbonized, part of the nitrogen will be retained in the carbon skeleton to form a nitrogen-doped carbon material, which effectively improves the electron distribution on the carbon surface and enhances the electron donating ability of the carbon material; at the same time, the doped nitrogen combines with carbon atoms to provide additional active sites for the graphite nitrogen catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the catalyst preparation process of an exemplary embodiment of the present application.
[0027] Figure 2 XRD diagram of the Ni-Mo2C catalyst prepared in Example 1-3 of the present application.
[0028] Figure 3 SEM images of Ni-Mo2C catalysts prepared for Example 1-3 of this application
[0029] Among them, Figure 3 Here, a, b, and c represent catalysts prepared from pine wood, corn, and soybean straw, respectively. DETAILED DESCRIPTION
[0030] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0031] It is particularly important to point out that similar substitutions and modifications made to the present application are obvious to those skilled in the art, and they are all deemed to be included in the present application. Relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present application to implement and apply the technology of the present application. Obviously, the described embodiments are only some embodiments of the present application, not all embodiments.
[0032] If no specific conditions are specified in this application, the preparation shall be carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials or excipients used, as well as the reagents or instruments used, for which the manufacturers are not specified, are all conventional products that can be obtained commercially.
[0033] The application is described in detail below.
[0034] The existing biomass resource utilization technologies mainly include incineration for heating, production of biogas, and production of alcohol using fermentation technology, but these technologies are only primary utilization of biomass, and the utilization efficiency is relatively low. In recent years, some emerging biomass utilization technologies have emerged, mainly including: production of synthetic gas, production of biodiesel, and gasification for power generation. However, for renewable, low-pollution, and widely distributed biomass, research in these fields cannot "eat up" the biomass well and develop its full potential. Therefore, it is necessary to develop applications in the field of catalysis based on the excellent surface properties of organisms, such as rich carbon content, high cation exchange capacity, large surface area, and stable structure.
[0035] The present application uses biomass as one of the raw materials and provides a method for preparing a biomass carbon-based Ni-Mo2C catalyst by carbonization reduction in an ammonia atmosphere. The catalyst is Ni-doped hexagonal Mo2C, which has high crystallinity, abundant active sites, and is a nano-sized catalyst with a porous structure.
[0036] The technical solution of the present application is introduced below in conjunction with specific embodiments.
[0037] Example 1
[0038] Take a certain amount of pine sawdust, use a wall breaker to crush it into powder, collect the part with a particle size less than 40 mesh, and place it in an oven at 105℃ to dry overnight to remove moisture.
[0039] 3.06g of pinewood powder, 3.06g of ammonium molybdate and 0.06g of nickel nitrate hexahydrate were taken into a beaker respectively, and 100mL of deionized water was added. The beaker was placed on a magnetic stirrer and stirred at 800r / min for 8h, and then ultrasonically mixed for 2h to ensure that the ammonium molybdate and nickel nitrate hexahydrate were completely dissolved and mixed with the pinewood powder. After the mixing was completed, the water in the beaker was evaporated and transferred to a vacuum oven to be dried overnight at 80°C to obtain a catalyst precursor.
[0040] The dried precursor was ground into powder, transferred to a porcelain boat, heated to 700°C at 5°C / min in a tubular heating furnace under NH3 atmosphere and maintained for 2h, then cooled to room temperature; and passivated with 1% O2 for 10h. The obtained black powder was the biomass-based Ni-Mo2C catalyst.
[0041] Example 2
[0042] Take a certain amount of corn kernels, use a wall breaking machine to crush them into powder, collect the part with a particle size less than 40 mesh, and place them in an oven at 105°C to dry overnight to remove moisture.
[0043] 3.06g corn powder, 3.06g ammonium molybdate and 0.06g nickel nitrate hexahydrate were taken into a beaker respectively, 100mL deionized water was added, the beaker was placed on a magnetic stirrer, stirred at 800r / min for 8h, and then ultrasonically mixed for 2h to ensure that ammonium molybdate and nickel nitrate hexahydrate were completely dissolved and mixed with corn powder. After the mixing was completed, the water in the beaker was evaporated and transferred to a vacuum oven to dry overnight at 80°C to obtain a catalyst precursor.
[0044] The dried precursor was ground into powder, transferred to a porcelain boat, heated to 700°C at 5°C / min in a tubular heating furnace under NH3 atmosphere and maintained for 2h, then cooled to room temperature; and passivated with 1% O2 for 10h. The obtained black powder was the biomass-based Ni-Mo2C catalyst.
[0045] Example 3
[0046] Take a certain amount of soybean straw, use a wall breaking machine to crush it into powder, collect the part with a particle size less than 40 mesh, and place it in an oven at 105°C to dry overnight to remove moisture.
[0047] 3.06g soybean straw powder, 3.06g ammonium molybdate and 0.06g nickel nitrate hexahydrate were taken into a beaker respectively, and 100mL deionized water was added. The beaker was placed on a magnetic stirrer and stirred at a speed of 800r / min for 8h, and then ultrasonically mixed for 2h to ensure that ammonium molybdate and nickel nitrate hexahydrate were completely dissolved and mixed with the soybean straw powder. After the mixing was completed, the water in the beaker was evaporated and transferred to a vacuum oven to be dried overnight at 80°C to obtain a catalyst precursor.
[0048] The dried precursor was ground into powder, transferred to a porcelain boat, heated to 700°C at 5°C / min in a tubular heating furnace under NH3 atmosphere and maintained for 2h, then cooled to room temperature; and passivated with 1% O2 for 10h. The obtained black powder was the biomass-based Ni-Mo2C catalyst.
[0049] Comparative Example 1
[0050] The preparation steps are the same as those in Example 3, except that the nickel-molybdenum ratio is not within the scope of this application.
[0051] Take a certain amount of soybean straw, crush it into powder, collect the part with particle size less than 40 mesh, and place it in an oven at 105°C to dry overnight to remove moisture.
[0052] Take 3.06g soybean straw powder, 3.06g ammonium molybdate and 0.6g nickel nitrate hexahydrate into a beaker, add 100mL deionized water, place the beaker on a magnetic stirrer, stir at 800r / min for 8h, and then ultrasonically mix for 2h to ensure that ammonium molybdate and nickel nitrate hexahydrate are completely dissolved and fully mixed with the soybean straw powder. After mixing, evaporate the water in the beaker and transfer it to a vacuum oven to dry overnight at 80°C to obtain a catalyst precursor.
[0053] The dried precursor was ground into powder, transferred to a porcelain boat, heated to 700°C at 5°C / min in a tubular heating furnace under NH3 atmosphere and maintained for 2h, then cooled to room temperature; and passivated with 1% O2 for 10h. The obtained black powder was the biomass-based Ni-Mo2C catalyst.
[0054] Comparative Example 2
[0055] The preparation steps are the same as those in Example 1, except that the reaction raw materials are pine wood powder and ammonium molybdate (ie, nickel nitrate hexahydrate is not added).
[0056] Take a certain amount of pine sawdust, use a wall breaker to crush it into powder, collect the part with a particle size less than 40 mesh, and place it in an oven at 105℃ to dry overnight to remove moisture.
[0057] Take 3.06g soybean straw powder and 3.06g ammonium molybdate into a beaker, add 100mL deionized water, place the beaker on a magnetic stirrer, stir at 800r / min for 8h, and then ultrasonically mix for 2h to ensure that the ammonium molybdate is completely dissolved and fully mixed with the soybean straw powder. After the mixing is completed, evaporate the water in the beaker and transfer it to a vacuum oven to dry overnight at 80°C to obtain a catalyst precursor.
[0058] The dried precursor was ground into powder, transferred to a porcelain boat, heated to 700°C at 5°C / min in a tubular heating furnace under NH3 atmosphere and maintained for 2h, then cooled to room temperature; and passivated with 1% O2 for 10h. The obtained black powder was the biomass-based Mo2C catalyst.
[0059] Comparative Example 3
[0060] The preparation steps are the same as those in Example 2, except that the reaction raw materials are corn powder and ammonium molybdate (ie, nickel nitrate hexahydrate is not added).
[0061] Take a certain amount of corn kernels, use a wall breaking machine to crush them into powder, collect the part with a particle size less than 40 mesh, and place them in an oven at 105°C to dry overnight to remove moisture.
[0062] Take 3.06g corn powder and 3.06g ammonium molybdate into a beaker, add 100mL deionized water, place the beaker on a magnetic stirrer, stir at 800r / min for 8h, and then ultrasonically mix for 2h to ensure that the ammonium molybdate is completely dissolved and fully mixed with the corn powder. After the mixing is completed, evaporate the water in the beaker and transfer it to a vacuum oven to dry overnight at 80°C to obtain a catalyst precursor.
[0063] The dried precursor was ground into powder, transferred to a porcelain boat, heated to 700°C at 5°C / min in a tubular heating furnace under NH3 atmosphere and maintained for 2h, then cooled to room temperature; and passivated with 1% O2 for 10h. The obtained black powder was the biomass-based Mo2C catalyst.
[0064] Comparative Example 4
[0065] Preparation of non-biomass supported nickel-molybdenum bimetallic catalysts.
[0066] 3.06g of melamine, 3.06g of ammonium molybdate and 0.06g of nickel nitrate hexahydrate were taken into a beaker respectively, and 100mL of deionized water was added. The beaker was placed on a magnetic stirrer and stirred at a speed of 800r / min for 8h, and then ultrasonically mixed for 2h to ensure that the ammonium molybdate and nickel nitrate were completely dissolved and mixed with the melamine. After the mixing was completed, the water in the beaker was evaporated and transferred to a vacuum oven to be dried overnight at 80°C to obtain a catalyst precursor.
[0067] The dried precursor was ground into powder, transferred to a porcelain boat, heated to 700°C at 5°C / min in a tubular heating furnace under NH3 atmosphere and maintained for 2h, then cooled to room temperature; and passivated with 1% O2 for 10h. The obtained black powder was Ni-Mo2C@NC catalyst.
[0068] Experimental example
[0069] 1. Test the XRD and SEM images of the catalysts of Examples 1-3 of the present application
[0070] like Figure 2 As shown in the figure (where A, B, and C correspond to Examples 1, 2, and 3, respectively), the peak of β-molybdenum carbide can be seen, proving the presence of molybdenum carbide and its high crystallinity, but A and B also have peaks of molybdenum oxide, which may be due to the fact that part of the molybdenum oxide has not been carbonized, resulting in the purity of molybdenum carbide being lower than that of C, which is also the reason why the catalytic performance of A and B is worse than that of C; in addition, due to the small amount of nickel added and the high dispersion of nickel, no obvious characteristic diffraction peak of Ni can be seen in the XRD of the two catalysts AC, while in B, it may be due to the sintering and agglomeration of nickel atoms during preparation, resulting in reduced activity, and a weak characteristic diffraction peak of Ni is shown on the XRD.
[0071] like Figure 3 As shown in the figure, the catalyst is composed of some irregular small particles, and some of them are agglomerated. The characteristics of the supported catalyst are clearly visible, with some small particles distributed on a large piece of carbon support, and the block is partially composed of loosely distributed small particles. This morphological difference indicates that the gas atmosphere plays a key role in the formation of the morphology during the pyrolysis of ammonium molybdate and biomass straw.
[0072] 2. The catalysts of the embodiments and comparative examples were tested for catalytic performance respectively, the method is as follows:
[0073] The catalyst was tableted and crushed to 40-60 mesh, and 0.5g of the catalyst was reacted with 2g of quinoline in 100mL of n-heptane solvent, in a pure hydrogen atmosphere, at a reaction temperature of 360°C (heating rate of 10°C / min), a pressure of 4MPa, and a reaction time of 2h. The test results are shown in the following table:
[0074] Quinoline conversion rate (%) Denitrification rate (%) Aromatic hydrocarbon selectivity (%) Example 1 99.9 98.7 83.2 Example 2 99.9 92.6 80.2 Example 3 99.9 99.9 87.3 Comparative Example 1 85.2 79.5 75.6 Comparative Example 2 79.7 75.6 72.2 Comparative Example 3 84.8 80.6 73.6 Comparative Example 4 76.5 68.5 70.2
[0075] According to the data in the above table, it can be seen that the biomass bimetallic catalyst of the present application has high quinoline conversion rate and denitrification rate, and good aromatic compound selectivity. In Comparative Example 1, the amount of nickel nitrate hexahydrate added is relatively large, resulting in a large difference in the nickel-molybdenum ratio, which has a great impact on the quinoline conversion rate, high denitrification rate and aromatic hydrocarbon selectivity of its catalyst. Compared with the catalyst added with nickel, the catalytic performance of the catalysts in Comparative Examples 2 and 3 has a certain decline, which proves that the addition of nickel improves the catalytic performance to a certain extent. In Comparative Example 4, the carrier is melamine instead of a biomass carrier, and the catalytic performance of the catalyst prepared in this comparative example is significantly lower than that of all biomass-based catalysts, proving that the biomass carbon source is better than the organic compound-based.
[0076] The description of the above embodiments is only used to help understand the method and core idea of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.
Claims
1. A method for preparing a biomass bimetallic catalyst, characterized in that: include: The biomass, ammonium molybdate and nickel nitrate hexahydrate are mixed and dried to obtain a catalyst precursor; Grinding the catalyst precursor to obtain catalyst precursor powder; The catalyst precursor powder is carbonized and passivated to obtain a biomass-based Ni-Mo2C catalyst.
2. The preparation method according to claim 1, characterized in that: The ratio of the amount of the ammonium molybdate to the amount of the nickel-molybdenum substance in the nickel nitrate hexahydrate is 1:100-1:10; The mass ratio of the biomass to the ammonium molybdate is 2:1-1:
2.
3. The preparation method according to claim 1, characterized in that: The drying temperature is 60-100°C.
4. The preparation method according to claim 1, characterized in that: The carbonization comprises: carbonization at 650-900° C. for 1-3 hours under NH 3 atmosphere.
5. The preparation method according to claim 4, characterized in that: The heating rate of the carbonization is 5°C / min.
6. The preparation method according to claim 1, characterized in that: The passivation includes: passivating with O2 having a volume concentration of 1% for 4-8 hours.
7. The preparation method according to claim 1, characterized in that: The biomass includes wood, straw, and food crops; Optionally, the biomass powder has a size smaller than 40 mesh.
8. A biomass bimetallic catalyst, characterized in that: The catalyst comprises: an active component and a carrier; The carrier is biochar; the active component is Ni-doped Mo2C; Among them, the molar ratio of nickel and molybdenum is 1:100-1:10, and the mass ratio of biomass and ammonium molybdate is 2:1-1:
2.
9. The biomass bimetallic catalyst according to claim 8, characterized in that: The biomass bimetallic catalyst is a nanocatalyst; The size of the biomass bimetallic catalyst is 3-5 nm.
10. Use of a biomass bimetallic catalyst prepared by the preparation method according to any one of claims 1 to 7, and / or a biomass bimetallic catalyst according to any one of claims 8 to 9, in the hydrodenitrogenation reaction of bio-crude oil to produce aromatic compounds.
